1998
DOI: 10.1021/es971124n
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Estrogen- and TCDD-Like Activities in Crude and Fractionated Extracts of PM10 Air Particulate Material Using in Vitro Gene Expression Assays

Abstract: Polar and nonpolar fractions prepared from an organic extract of inhalable air particulate material collected from an urban location in downtown Toronto, Ontario, Canada, were examined for estrogen and Ah receptor-mediated activities using in vitro gene expression assays. The presence of estrogenic activity was determined using MCF-7 human breast cancer cells transiently transfected with a Gal4-human estrogen receptor chimera and a Gal4-regulated luciferase reporter gene. 2,3,7,8-Tetracholordibenzo-p-dioxin (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
134
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(146 citation statements)
references
References 88 publications
(111 reference statements)
8
134
1
2
Order By: Relevance
“…The chemical analysis of PM 10 extracts collected from Advance showed that the concentration of most PAHs were higher than the average ambient concentration reported for Toronto (Clemons et al 1998) and in some cases for Denver, Colorado (Chow et al 1998). However, PAH concentrations at Advance were consistently lower than those found in Santiago (Gil et al 2000).…”
Section: Discussionmentioning
confidence: 90%
“…The chemical analysis of PM 10 extracts collected from Advance showed that the concentration of most PAHs were higher than the average ambient concentration reported for Toronto (Clemons et al 1998) and in some cases for Denver, Colorado (Chow et al 1998). However, PAH concentrations at Advance were consistently lower than those found in Santiago (Gil et al 2000).…”
Section: Discussionmentioning
confidence: 90%
“…Thus we got one sample to represent APM on a sunny day and two samples to represent APM at foggy days. The composite samples were extracted with dichloromethane and acetone (1:1) for 24 h using a Soxhlet apparatus to afford crude extracts that were fractionated according to procedure which was a slightly modified version of that described by Clemons et al (1998).…”
Section: Air Particulate Collection and Fractionationmentioning
confidence: 99%
“…Urban air particulate material (APM) is a complex mixture of chemicals released from vehicular and industrial sources, together with oil fumes from house cooking and re-entrained particles from roads. A study has discovered estrogenic activities present in air particulate material using in vitro gene expression assays (Clemons et al, 1998). However, little information is available on the changes of estrogenic activities in APM under different weather conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some in vitro assays that act through the ER mode, such as the E-Screen-assay, the yeast estrogen screen (YES)-assay or receptor binding-assays, have been developed to screen for estrogenic or anti-estrogenic activity of chemicals (Bolger et al, 1998;Gaido et al, 1997;Payne et al, 2000). These biological methods have been previously used to detect the estrogenic activity in complex extracts from environmental samples, such as pulp and paper mill sludge and effluents, and particulate matter in air and sediments (Clemons et al, 1998;Koistinen et al, 1998). In most studies, only a few active agents were identified due to the complex composition of the samples (Koh et al, 2005;Legler et al, 2002).…”
Section: Introductionmentioning
confidence: 99%